Du Scorpion au Désert, Albert Memmi revisited - Isaac Yetiv (Studies in 20th & 21st Century Literature, 1982)
Albert Memmi's literary work of the last three decades is pervaded by a fundamental pessimism on life and the human condition. It is a long, never-ending investigation of the dynamics of conflict, its causes and its disastrous consequences: hatred, violence, death. In the last decade, with the publication of Le Scorpion (1969), and Le Désert (1977), Memmi seems to have reached his long-proclaimed goal, "the extrapolation of a personal experience to universal dimensions." These two novels do not reveal a radical departure from the young Memmi's outlook on life. Their innovation lies in the originality of their structure, composition and style, and in the abundant use of technical devices. There is almost no plot in Le Scorpion and Le Désert. Autobiographical elements, preponderant in his early novels, are buried in an incoherent narrative loosely anchored in a nebulous context of time and space. The "story" does not follow a linear development. Chronology and geography are manipulated at will in imaginary settings. The characters evolve in imaginary spaces and, as in a conte fantastique, the narration of their exploits and perilous adventures serves the only purpose of sustaining and illustrating the author's philosophical ideas. In Le Scorpion, the author's multifaceted personality is represented by different characters who take part in the dialogues and contribute to the elaboration of the author's philosophy.
Keywords: Albert Memmi; conflict; hatred; violence; death; Le Scorpion; Le Désert; personal experience; universal dimensions; technical devices; Autobiographical; conte fantastique